LED power efficiency of biomass, fatty acid, and carotenoid production in Nannochloropsis microalgae. (March 2018) - Ma, Ruijuan; Thomas-Hall, Skye R.; Chua, Elvis T.; Eltanahy, Eladl; Netzel, Michael E.; Netzel, Gabriele; Lu, Yinghua; Schenk, Peer M.
Graphical abstract: Highlights: First study linking algal fatty acid yield and power efficiency under various LEDs. LEDs can be fine-tuned to grow Nannochloropsis algae more energy-efficiently. Biomass and fatty acid yields were similar for high and low intensity LEDs. Low light red LEDs were most power efficient for biomass and fatty acids. White LEDs were least power efficient for biomass, fatty acid, and carotenoids. Abstract: The microalga Nannochloropsis produces high-value omega-3-rich fatty acids and carotenoids. In this study the effects of light intensity and wavelength on biomass, fatty acid, and carotenoid production with respect to light output efficiency were investigated. Similar biomass and fatty acid yields were obtained at high light intensity (150 μmol m −2  s −1 ) LEDs on day 7 and low light intensity (50 μmol m −2  s −1 ) LEDs on day 11 during cultivation, but the power efficiencies of biomass and fatty acid (specifically eicosapentaenoic acid) production were higher for low light intensity. Interestingly, low light intensity enhanced both, carotenoid power efficiency of carotenoid biosynthesis and yield. White LEDs were neither advantageous for biomass and fatty acid yields, nor the power efficiency of biomass, fatty acid, and carotenoid production. Noticeably, red LED resulted in the highest biomass and fatty acid power efficiency, suggesting that LEDs can be fine-tuned to grow Nannochloropsis algae more energy-efficiently.